Analisis Semiotika Makna Kehilangan dalam Lirik Lagu “Cutting My Fingers Off” Oleh Turnover: Analisis Semiotika Ferdinand De Saussure - Ramadhan, Muhamad Fajar Ramadhan (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research aims to understand how the meaning of loss is constructed in the lyrics of the song “Cutting My Fingers Off” by Turnover, using Ferdinand de Saussure’s semiotic approach. The song was chosen as the object of study because it expresses the emotion of loss intensely through poetic and emotional lyrical symbols. According to Saussure’s theory, meaning is formed through the relationship between the signifier and the signified, where words in the lyrics function as signs that carry deep meaning. This study uses a descriptive qualitative method with interview, textual analysis techniques, supported by literature review and observation of listener Turnover’s “Cutting My Fingers Off”. The analysis involves breaking down each verse to identify signifiers and signifieds that shape the emotional meaning of loss. The findings show that the lyrics reflect not only physical loss but also psychological experiences such as alienation, regret, and severed emotional attachment. Symbols like “Cutting My Fingers Off” form a visual metaphor for deep emotional pain. This research concludes that music particularly lyrics is an effective medium of symbolic communication to convey personal experiences. “Cutting My Fingers Off” successfully constructs a complex meaning of loss that resonates personally with its listeners.